Relationship between diabetic retinopathy microalbuminuria and other modifiable risk factors. Issue 3 (June 2021) - Chawla, Shubhaa; Trehan, Siddhant; Chawla, Aastha; Jaggi, Shalini; Chawla, Rajeev; Kumar, Vinay; Singh, Depender
Highlights: Retinopathy, microalbuminuria, and peripheral neuropathy coexist with the microvascular complications of type 2 diabetes. Large cohort of 3090 patients in the real world setting has demonstrated the simultaneous association of diabetic retinopathy with nephropathy and neuropathy. Our study highlights the need for monitoring for microalbuminuria that could be marker for the development of proliferative diabetic retinopathy. Abstract: Background: Diabetic Retinopathy (DR) is an important microvascular complication of diabetes that can lead to irreversible blindness. Microalbuminuria is strongly associated with diabetic retinopathy and can be used as a reliable marker of diabetic retinopathy. Aim: To assess the association between DR, microalbuminuria, and other modifiable risk factors in patients with type 2 diabetes. Methodology: 3090 patients with T2DM visiting North Delhi Diabetes Centre, New Delhi between July 2016 to October 2019 were evaluated for the clinical and biochemical parameters that included urinary albumin, HbA1C, lipid profiles, serum creatinine estimation and underwent biothesiometry. Results: 3090 patients (1350 females and 1740 males), with mean age of 52.7 ± 9.2 years and diabetes duration ranging from 1 to 19 years (mean 9.4 ± 6), duration of less than 5 years, 6–10 years and more than 10 years in 52%, 26% and in 22%, respectively. Duration of diabetes was strong predictor of retinopathy (p = 0.001). The HbA1c and BMI in patients with DR was significantly higher than in those without DR. 18.2% patients were diagnosed to have retinopathy. Peripheral neuropathy was observed in 24.2% and was positively associated with DR (p = 0.002). 33.9% and 4.5% patients had microalbuminuria macroalbuminuria, respectively and 9.7% patients had creatinine >1.3 mg/dL. There was significant positive relationship between different grades of retinopathy and albuminuria. Conclusions: Our study is a large real-world study that demonstrates that HbA1c, BMI, duration of diabetes, microalbuminuria and peripheral neuropathy are relatively, yet cohesively contributing factors towards varying grade of retinopathy.